2009
DOI: 10.1002/art.24653
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of red blood cell methotrexate polyglutamate concentrations in rheumatoid arthritis patients receiving long‐term methotrexate treatment

Abstract: Objective. Methotrexate (MTX) is the most commonly used disease-modifying antirheumatic drug (DMARD) in the management of rheumatoid arthritis (RA). MTX is transported into cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
60
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 29 publications
11
60
1
7
Order By: Relevance
“…Like Stamp and colleagues, we found that the dose of MTX (in mg/kg) had a better correlation with longer chain MTXGlu 3-5 compared with lower order polyglutamates, with higher doses of MTX associated with higher concentrations of the long-chain polyglutamates (results not shown). Stamp et al hypothesized that the time to reach steady state may play a part in this phenomenon, with the longer chain subtypes revealing a more apparent relationship with dose compared with the shorter chain subtypes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Like Stamp and colleagues, we found that the dose of MTX (in mg/kg) had a better correlation with longer chain MTXGlu 3-5 compared with lower order polyglutamates, with higher doses of MTX associated with higher concentrations of the long-chain polyglutamates (results not shown). Stamp et al hypothesized that the time to reach steady state may play a part in this phenomenon, with the longer chain subtypes revealing a more apparent relationship with dose compared with the shorter chain subtypes (20).…”
Section: Discussionmentioning
confidence: 99%
“…MTX is one of the most commonly used antirheumatic medications (21), as mono-therapy or in combination with the disease modifying drugs (LMB) because of its therapeutic efficiency and toxicity profile (6). The antiinflammatory effect of MTX is mediated by adenosine receptors stimulation (22,23) so the determination of ADA catalytic activities is significant in monitoring the metabolism and therapy effects of MTX.…”
Section: Introductionmentioning
confidence: 99%
“…There is now some evidence that MTX-polyglutamate (MTX-PG) levels in patients with RA may be related to efficacy 2,3,4,5,6,7 , although not all investigators have reached the same conclusions 8 . Nevertheless, researchers are rightfully examining the factors that affect the accumulation of MTX-PG, which could lead to important insights into their contribution to the therapeutic effects of MTX.…”
mentioning
confidence: 99%